KOMUNIKASI KRISIS PEMERINTAH KABUPATEN TEMANGGUNG DALAM MENGHADAPI PANDEMI COVID-19 - Andi Rizqi Mubaroq; Wijayanto - -; Supratiwi - - (Journal of Politic and Government Studies, 2021)
Crisis communication is carried out to gain trust in the community and to assure the public that the crisis can be resolved immediately. Therefore, this study aims to find out about the implementation carried out by the Temanggung Regency Government using the theory of crisis and emergency risk communication, with five existing stages, namely, the pre-crisis phase, the beginning of the crisis, the crisis, resolution, and evaluation. Situational crisis communication theory is also used in this study to find out instructive information and adjustment information from the government. This study also aims to find out what media are used by the Temanggung Regency Government in communicating the COVID-19 crisis, the effectiveness of crisis communication, as well as the barriers and challenges of crisis communication. This study used a descriptive qualitative research approach with data collection techniques by interviewing Irham Syafii, Sri Endang, Agung Aristyo, and Djoko Prasetiyono brothers. In this study, the main findings were found, namely, all crisis communication activities were carried out with the preparation of the right materials and materials, then carried out with the correct implementation according to the rules, and evaluation of the progress of communication. It aims to make crisis communication run as expected.